Figure 2 from: Shandikov G, Eakin R (2013) Pogonophryne neyelovi, a new species of Antarctic short-barbeled plunderfish (Perciformes, Notothenioidei, Artedidraconidae) from the deep Ross Sea. ZooKeys 296: 59-77. https://doi.org/10.3897/zookeys.296.4295 - Shandikov, Gennadiy; Eakin, Richard (Zenodo, 2013)
Figure 2 - Mental barbel in short-barbeled species of the "Pogonophryne mentella" group, dorsal view, showing processes from various regions of terminal expansion; arrow indicates upper border of terminal expansion: a Pogonophryne tronio, holotype (MKhNU R295, formalin-preserved), male, 295 mm SL b Pogonophryne neyelovi sp. n., holotype (formalin-preserved) c Pogonophryne brevibarbata, female (MKhNU R298, just caught specimen), 262 mm SL d Pogonophryne ventrimaculata, holotype ZMH 46-1985, alcohol-preserved (from Eakin 1987: fig. 4), female, 214 mm SL. Scale bar 1 mm.